Preparation of β-glucan scaffolds by hydrogel foaming with supercritical CO2 - Salgado, M. (2016)
New materials and processing techniques are being constantly developed for the production of scaffolds for tissue engineering applications. Traditionally, foaming of polymers with supercritical fluids is one of the procedures used to create porous matrices. However, this technique cannot be applied to hydrophilic polymers which suffer degradation below their melting temperature. Foaming of hydrogels is an alternative to conventional gas foaming for the processing of hydrophilic polymers by dissolution of supercritical CO2 in the water of the hydrogels [1]. Through a fast depressurization, a highly porous structure is obtained, which results in the foamed matrix of polymer after water removal. In this work, Î²-glucan aerogels are produced by hydrogel foaming with supercritical CO2. Among polysaccharides, Î²-glucans have not been widely explored yet for tissue engineering applications. Depending on their origin, they posses different structures and properties. In our study, hydrogels were created from barley and yeast Î²-glucans. The produced aerogels were characterized in terms of morphology, mechanical properties and degradation rate in physiological fluids.